The effect of physical education lesson on aggressive behavior and some components of physical fitness among high school students (Journal of the College of Basic Education, 2022)
The research aims to: Preparing sports activities (classroom (systematic) and not classroom such as work (tournaments between classes)). And his knowledge of the effect of sports activity on the aggressive behavior of second-grade students at Al-Firdous High School for Girls. And its knowledge of the effect of sports activity on some components of physical fitness among second-grade students at Al-Firdous Secondary School for Girls. The researcher chose the experimental method (with one group) as it is more suitable with the research problem. The sample was chosen (89) female students from the second grade intermediate from among the female students of Al-Firdous Secondary School for Girls in Baghdad / Al-Amiriya. The researcher conducted the pre-tests, and the aggressive behavior scale and physical fitness tests were applied to the research sample. After 8 weeks, the researcher conducted the post tests and the data were processed statistically and after the presentation and discussion, the researcher reached the following conclusions: That the physical education study has a direct effect in reducing the aggressive behavior of Female second graders. The physical education lesson has a direct effect on some components of physical fitness. Significant differences appeared statistically significant in the proportion of aggressive behavior in favor of the post-test. Significant differences appeared with statistical significance in physical fitness tests in favor of post tests